La géographie et la question régionale : le complexe géographique entre régionalisation et internationalisation de l'espace - Raimundo Nonato Junior (Confins)
This article presents some results and discussions of the thesis "Regional geography of the Brazil-France border: the tension between regionalization and internationalization of the Oyapock area", emphasizing the importance of regional analysis for contemporary research in geography. The results show that regional relations in the Franco-Brazilian border are present like a "geographical complex" that articulates the interests of different players, social groups and scales. They also reveal the power appointed by the Regional Geography to establish contemporary dialogues between the epistemology of geographical science and fieldwork, putting into relation the physical, human, historical, political and everyday dimensions that are present in the multiplicity of socio-spatial relations.